IMPLEMENTASI KEBIJAKAN PROGRAM PEMBERDAYAAN KESEJAHTERAAN KELUARGA (PKK) DALAM MENINGKATKAN PEMBERDAYAAN PEREMPUAN DI DESA SUKAMANTRI KECAMATAN CISAAT KABUPATEN SUKABUMI - Santi Legianti Sutandi (Jurnal Dialektika Politik, 2023)
Building a development program in the community, in its implementation it is essential to pay a lot of attention to the participants who will receive the empowerment. This is so that the receipt of information becomes balanced and equal between participants who have different ways of thinking as a result of different life experiences. This is done so that the community empowerment program implemented can be carried out properly. In this case, the research focuses on the problem of policy implementation of the Family Welfare Empowerment Program (PKK) in Sukamantri Village related to women's empowerment. In qualitative research, the problems brought by researchers are still dim, even though they are still dark, complex and dynamic. Therefore, problems in this research are still tentative and will be developing or changing after the researcher is in the field.